A Scientific analysis of Various forms of Chemical Compounds and their use - Prof. Romi Morzelona (Forest Chemicals Review, 2018)
In this Research it is talked about that different procedure of Portland concrete assembling. Wet procedure minerals are wet ground to shape a slurry and in dry procedure minerals are dry ground to frame a powder like substance. In this paper, we are talking about the correlation between wet procedure and dry procedure with different favorable circumstances and drawbacks.